High aspect ratio nanoscale multifunctional materials derived from hollow carbon nanofiber by polymer insertion and metal decoration - Balan, Beena K.; Kale, Vinayak S.; Aher, Pradnya P.; Shelke, Manjusha V.; Pillai, Vijayamohanan K.; Kurungot, Sreekumar (Chemical Communications, 2010)
A novel high aspect ratio material which can simultaneously display multiple functions such as proton and electron conductivity and electrocatalytic activity has been developed by incorporating both platinum nanoparticles and phosphoric acid doped polybenzimidazole along the inner and outer surfaces of a hollow carbon nanofiber.